THE INFLUENCE OF THE AMBIANCE ON THE DEVELOPMENT OF POETIC THINKING OF THE ARTIST - Rakhimovna, Umarova Nuriniso (PT. Antis International Publisher, 2024)
In this article we strive to describe one of the largest representatives of Uzbek literature, Abdulla Oripov’s poetry collection which was published after his death. “The Birth of a Poet” excitedly recalls his childhood impressions, the beauty of Mother Nature, and the moments that left a deep mark on his life, heart, and poetically written in verse and about his childhood in the formation of an artist as a person, as a creator, how it went, and the role of the environment in which he was born and grew up in the development of the writer became important